1979
DOI: 10.1177/004051757904900609
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Thermomechanical and Chemomechanical Texturing of Nylon 6 Multifilament Yarns

Abstract: Nylon 6 multifilament yarn is textured by both the conventional false-twist method and a new method of solventtexturing with aqueous phenol. The physical, mechanical, and structural properties of the textured yarns are compared.It is observed that the solvent-textured yarn has a considerably higher dye uptake than the conventionally-textured yarn. SEM studies reveal interesting differences in the surface characteristics of fibers textured by the two processes. ' ' ' ~ --Introduction 'The texturing process invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In a recent publication we showed that cotton yarns can also be textured through a decrystallization-recrystalliia.tion cycle following a chemomechanical route [8]. We also reported that thermoplastic yarns can be textured by setting through solvent-induced crystallization [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication we showed that cotton yarns can also be textured through a decrystallization-recrystalliia.tion cycle following a chemomechanical route [8]. We also reported that thermoplastic yarns can be textured by setting through solvent-induced crystallization [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Two reasons that solvent texturing is of interest are its potential for energy savings [ 2 ] and a considerably higher dye uptake [ 4,5].…”
mentioning
confidence: 99%